The Use of Molecular Techniques in Isolation and Characterization of Mycoplasma gallisepticum from Commercial Chickens in Jordan - Gharaibeh, Saad; Roussan, Dirgham Al (International Journal of Poultry Science, 2007)
Commercial chickens in Jordan suffer from respiratory disease of undetermined etiology. This study was designed to document the involvement of Mycoplasma gallisepticum (MG) in this respiratory disease. Seventy six different chicken flocks with respiratory symptoms (48 broiler flocks, 21 layer flocks and 7 broiler-breeder flocks) were examined serologically by commercial MG ELISA kit and bacterial isolation for Mycoplasma. Twenty four MG isolates from 76 flocks were cloned and the presence of MG in the cloned cultures was confirmed by polymerase chain reaction. The isolates were further examined using Random Amplified Polymorphic DNA (RAPD) technique. The prevalence of MG in the flocks examined was 73.5% and 31.6% by ELISA and isolation, respectively. This high prevalence in flocks with respiratory disease, confirms the endemic nature of the disease in Jordan. RAPD testing of the 24 isolates revealed the presence of 5 banding patterns that were different than the common MG F strain vaccine used in the field. This is the first study to isolate and characterize MG from chickens in Jordan.